Trends in reproductive and maternal healthcare indicators, Côte d’Ivoire, 2018 to 2020 - Denise O.D. Kpebo; Marie-Dorothée Mélèdje Koffi-Koumi; Marie-Laurette Agbré-Yacé; Jean-Ernest D. Kamenan; Odile S. Aké-Tano; William Yavo; Gouda R.M. Mady; Diarra B. Senghor; Cheikh M. Faye (Journal of Public Health in Africa)
Background: Despite some improvement, there are still persistent challenges in the area of reproductive and maternal health in Côte d’Ivoire.